VD_FINDINFO HC / 2019 / 351 vom 15. April 2019 - VD Tribunal cantonal (2019)
OBLIGATION D'ENTRETIEN, ENFANT, MODIFICATIONEN GÉNÉRAL, TRAIN DE VIE, AVANCE DE FRAIS, CONJOINT | 176 al. 1 CC, 179 al. 1 CC, 276 al. 1 CC, 285 al. 1 CC